2018
DOI: 10.30848/pjb2019-2(28)
|View full text |Cite
|
Sign up to set email alerts
|

Integration of cytological and molecular analysis to confirm a hybridity in F1 Brassica progeny

Abstract: In Brassica, interspecific hybridization is a potential and useful method for transferring valuable traits between species of commercial interest. In the previous experiments successful interspecific hybrids were obtained through hybridization between chosen rapeseed cultivars (Brassica napus L.) and Brassica rapa genotypes for transferring clubroot resistance from wild species into cultivated background. In the presented research morphological, cytological and simple sequence repeats (SSR)based molecular anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Additionally, high efficiency of PCR-based molecular markers is cost effective and capable of replacing the high laborious GOT tests. And the crop (Indian Mustard) is being self-pollinated in nature, there are high 2009 [8] demonstrated the use of cytological and molecular marker for identification F 1 progeny in Brassica. Wang et al, 2002 [9] demonstrated the genetic purity of hybrid in Maize using SSR markers, in Rice (Nandakumar et al, 2004, Shanthala et al, 2013) [10,11] , in Tomato (Liu et al, 2008) [12] and in Brassica juncea (Sharma et al, 2018) [13] .…”
Section: Confirmation Of True Hybridmentioning
confidence: 99%
“…Additionally, high efficiency of PCR-based molecular markers is cost effective and capable of replacing the high laborious GOT tests. And the crop (Indian Mustard) is being self-pollinated in nature, there are high 2009 [8] demonstrated the use of cytological and molecular marker for identification F 1 progeny in Brassica. Wang et al, 2002 [9] demonstrated the genetic purity of hybrid in Maize using SSR markers, in Rice (Nandakumar et al, 2004, Shanthala et al, 2013) [10,11] , in Tomato (Liu et al, 2008) [12] and in Brassica juncea (Sharma et al, 2018) [13] .…”
Section: Confirmation Of True Hybridmentioning
confidence: 99%
“…chinensis was used as the female parent and Brassica napus as the male parent (Niemann et al, 2015). True F 1 hybrids between these species were intermediate in terms of morphological traits compared with the parental genotypes; however, in their pollen mother cells (PMCs), various abnormalities, such as univalent, lagging chromosomes and disorders in synchronization, were observed during meiosis (Niemann et al, 2019).…”
Section: Broadening the Variability Of Oilseed Rape Through Interspec...mentioning
confidence: 99%